Preparation and Challenges of Industry 5.0 for Small and Medium Enterprises in Indonesia - Kurniawan, Aries; Komara, Beni Dwi; Setiawan, Heri Cahyo Bagus (Muhammadiyah International Journal of Economics and Business, 2019)
The purpose of this study is to provide inputs for Small and Medium Enterprises (SMEs) in facing the era of Industry 5.0. Many perceive Industry 5.0 as a continuation of the fourth industrial revolution that utilizes ‘big data’ on the internet to run a business. The approach used in this study was literature study, which was intended to examine the current events, especially in the production process. A number of documentary videos from severalsources, including YouTube, National Geographic channel and other sources, were retrieved to examine the changes in the industrial trends in various parts of the world. As a result, it can be concluded that the challenges faced by SMEs in establishing business inIndustry 5.0 mainly relate to product excellence. Facing the new era, local SMEs have several advantages that have to be developed due to the involvement of human ‘touch’ in the businessprocesses. Some products are potentially irreplaceable despite the changes of industrial trend, namelyproducts with special characteristics such as handicrafts and natural resources based products.For SMEs in Indonesia, there are other advantages in addition to the special characteristics in theprocesses and final products, which are the national and cultural values of Indonesia